Feasibility of preference-driven radiotherapy dose treatment planning to support shared decision making in anal cancer. (3rd October 2017) - Rønde, Heidi S.; Wee, Leonard; Pløen, John; Appelt, Ane L.
Abstract: Purpose/Objective: Chemo-radiotherapy is an established primary curative treatment for anal cancer, but clinically equal rationale for different target doses exists. If joint preferences (physician and patient) are used to determine acceptable tradeoffs in radiotherapy treatment planning, multiple dose plans must be simultaneously explored. We quantified the degree to which different toxicity priorities might be incorporated into treatment plan selection, to elucidate the feasible decision space for shared decision making in anal cancer radiotherapy. Material and methods: Retrospective plans were generated for 22 anal cancer patients. Multi-criteria optimization handles dynamically changing priorities between clinical objectives while meeting fixed clinical constraints. Four unique dose distributions were designed to represent a wide span of clinically relevant objectives: high-dose preference (60.2 Gy tumor boost and 50.4 Gy to elective nodes with physician-defined order of priorities), low-dose preference (53.75 Gy tumor boost, 45 Gy to elective nodes, physician-defined priorities), bowel sparing preference (lower dose levels and priority for bowel avoidance) and bladder sparing preference (lower dose levels and priority for bladder avoidance). Results: Plans satisfied constraints for target coverage. A senior oncologist approved a random subset of plans for quality assurance. Compared to a high-dose preference, bowel sparing was clinically meaningful at the lower prescribed dose [median change in V45Gy : 234 cm 3 ; inter-quartile range (66; 247); p  < .01] and for a bowel sparing preference [median change in V45Gy : 281 cm 3 ; (73; 488); p  < .01]. Compared to a high-dose preference, bladder sparing was clinically meaningful at the lower prescribed dose [median change in V35Gy : 13.7%-points; (0.3; 30.6); p  < .01] and for a bladder sparing preference [median change in V35Gy : 30.3%-points; (12.4; 43.1); p  < .01]. Conclusions: There is decision space available in anal cancer radiotherapy to incorporate preferences, although tradeoffs are highly patient-dependent. This study demonstrates that preference-informed dose planning is feasible for clinical studies utilizing shared decision making.